Jonathan Harvey - Whittall, Arnold -1935 (London Faber and Faber, 1999)
The second in a series of handbooks on composers of today, aiming to introduce their work to a wide audience and to describe their creative development. Each volume includes a substantial interview with the composer and a comprehensive work list.Jonathan Harvey has been a leading and distinctive presence in British music since the 1960s. After studies with Erwin Stein and Hans Keller, Harvey, in his earliest works, explored the living English tradition extending from Britten to Maxwell Davies. At the same time, however, he was no less open to developments on the wider international scene, and his music has achieved as much success in continental Europe and America as it has in Britain. It is in his studio work, especially at IRCAM but at other institutions as well, that he has explored with particular persuasiveness the conjunction between technology and spirituality that gives his work its most individual quality.